Content Analysis of Mobile Health Applications on Diabetes Mellitus - Izahar, Syarafina; Lean, Qi Ying; Hameed, Mohammed Abdul; Murugiah, Muthu Kumar; Patel, Rahul P.; Al-Worafi, Yaser Mohammed; Wong, Tin Wui; Ming, Long Chiau (Frontiers in Endocrinology, 2017)
Diabetes self-management offers an opportunity to patients to be actively involved in managing their conditions and modifying lifestyle behaviours in order to attain positive health outcomes. With the unprecedented growth of mobile technology, smartphone play a role in supporting diabetes self-management. Nonetheless, selecting appropriate mobile applications (apps) is challenging for patients. Thus, this study aimed to evaluate and compare the contents and features of mobile medical apps for diabetes self-management. Of 346 commercial apps, 16 (16%) and 19 (7.72%) of the diabetes apps found in Apple and Google Play stores respectively were included based on the selection criteria and individually scored for the availability of eight main features of diabetes self-management. The apps supported self-management by offering features such as free installation, less than 50MB space used, offline use, automated data entry, data export and sharing, educational tool and advice. Of the eight evaluated features, only 11 (31.4%) apps had a score of five whereas 7 (20%) apps scored the lowest, with a score of three. The majority of apps were free, required no internet connectivity to use and were less than 50 MB in size. Our findings showed that the design of diabetes mobile apps focused on reporting and setting reminders, rather than providing personalised education or therapeutic support. In the future, the design of apps could be improved to integrate patients’ needs, usability for disease management and lifestyle modifications.